PENGARUH INDEKS BURSA REGIONAL TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Ekadjaja, Margarita (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
In relation with fast economical growth in Indonesia and followed by the growth of the stock exchange, investing in the stock exchange is become one of the profitable choices for the investor. The main indicator of Indonesian stock exchange performance is called IHSG. This research aiming to describe the correlation between regional index (STI Index and KLCI)and IHSG either simultaneously or partially in BEI. The samples used in this research is regional index during 2008-2012. Model of analysis used in this research is multiple regression analysis. Simultant used to test the influence from entire / all variable regional index to IHSG with significant level of 5%. The research stated that, simultaneously there was a significanct correlation between regional Index (STI and KLCI) to IHSG the Fhitung > Ftabel (326.4711 > 3,35). Partially there was significant correlation among STI and KLCI to IHSG and there was a significanct correlation among regional Index (STI and KLCI)to the IHSG the significancy in 5%.